2005
DOI: 10.1143/jjap.44.156
|View full text |Cite
|
Sign up to set email alerts
|

Structural Modulation in Oxygen Deficient Epitaxial Bi2Sr2Ca1Cu2OX Observed by X-ray Reciprocal Space Mapping

Abstract: X-ray reciprocal space mapping (XRSM) was employed to investigate the effect of oxygen deficiency on supercell (SC) modulation in an epitaxial Bi2Sr2Ca1Cu2O x (Bi-2212) single layer. Cross section XRSM (ω–2θ plane) was used to estimate both the lattice constants and SC periodicity in epitaxial Bi-2212, and plan view XRSM (ω–ψ plane) to verify the symmetry of an in-plane SC structure. The SC periodicity expanded along both the b- and c-axes on the Bi-2212 film post anneal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2005
2005
2007
2007

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…In this work, the SC periodicity expanded on films deposited even at higher oxygen pressure. The previous study [13] showed that SC periodicity expanded on oxygen-deficient Bi-2212 film. A possible explanation for the expansion of SC periodicity along both b and c axes is that the film was deposited under the condition of oxygen deficiency; even though the film was deposited at higher oxygen pressure, fewer ions exposed to the substrate resulted in oxygen-deficient condition.…”
mentioning
confidence: 88%
See 2 more Smart Citations
“…In this work, the SC periodicity expanded on films deposited even at higher oxygen pressure. The previous study [13] showed that SC periodicity expanded on oxygen-deficient Bi-2212 film. A possible explanation for the expansion of SC periodicity along both b and c axes is that the film was deposited under the condition of oxygen deficiency; even though the film was deposited at higher oxygen pressure, fewer ions exposed to the substrate resulted in oxygen-deficient condition.…”
mentioning
confidence: 88%
“…Recently, the XRSM method was used to investigate the SC structure in Bi-2212 films. Asymmetric distribution of satellite peaks generated by the SC structure was observed on XRSMs in epitaxial Bi-2212 thin films [12,13]. The influence of the SC periodicity on internal strain was also investigated on multilayered bismuth cuprate [14].…”
mentioning
confidence: 94%
See 1 more Smart Citation